Analisis UI pada Perancangan Aplikasi Perpustakaan Cerita Rakyat “Kisahnesia” dengan Metode System Usability Scale - Astawan, Putu Bagus Rangga Permana Putra; Ari Mogi, I Komang (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
In order to preserve Indonesian culture and raise reading interest, website named Kisahnesia was created. This study focuses on analyzing the User Interface (UI) of the Kisahnesia application using the System Usability Scale (SUS) methodology. The objective of the study is to assess the usability of the application and determine the level of user satisfaction. The SUS questionnaire was administered to a sample of users, and based on the analysis of the collected data, the application obtained a score of 78.375. This score indicates that the Kisahnesia application has passed the usability test, demonstrating a high level of usability and user satisfaction. The findings suggest that the UI design of Kisahnesia is effective in providing a user-friendly and intuitive experience, contributing to the overall positive user perception of the application's usability.